High-quality WS2film as a hole transport layer in high-efficiency non-fullerene organic solar cells - Wang X.; Liu P.; Yap B.; Xia R.; Wong W.-Y.; He Z. (Royal Society of Chemistry, 2023)
Conducting polymers; Efficiency; Fullerenes; Hole mobility; Indium compounds; Organic solar cells; Plasma applications; Sulfur compounds; Tin oxides; Transition metals; Ethylenedioxythiophenes; High quality; Higher efficiency; Higher yield; Hole transport layers; Initial concentration; Metal disulfide; Plasma treatment; Poly(styrene sulfonate); Yield quality; Tungsten compounds